INOVASI TEKNOLOGI EKONOMI YANG BERKELANJUTAN: STRATEGI, IMPLEMENTASI, DAN DAMPAKNYA BAGI PERTUMBUHAN HIJAU DI INDONESIA - Elisabet Tambunan; Sutriono; Muhammad Irsyad; R. Sabrina (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: The transformation toward a sustainable economy has become a strategic necessity amid the growing pressures of climate crisis, environmental degradation, and social inequality. Technological innovation is widely regarded as a key driver in balancing economic growth with environmental preservation and social inclusivity. This study aims to identify key technologies that support the sustainable economy, analyze their implementation strategies across major sectors in Indonesia, and evaluate their impact on the economic, environmental, and social dimensions (triple bottom line). This research employs a qualitative-descriptive approach through literature review and case analysis in the energy, agriculture, manufacturing, and MSME sectors. The findings indicate that artificial intelligence (AI), Internet of Things (IoT), big data, blockchain, renewable energy, and green fintech significantly contribute to improving resource efficiency, reducing emissions, enhancing supply chain transparency, and expanding access to green financing. However, several challenges remain, including infrastructure readiness, high initial investment costs, limited digital literacy, non-adaptive regulatory frameworks, and unequal access to technology. This study recommends strengthening incentive-based policies, developing cross-sector innovation ecosystems, and enhancing green-digital human resource capacities to accelerate the growth of a sustainable economy in Indonesia. Keywords: Sustainable Economy, Technological Innovation, Green Economy, Circular Economy, Indonesia, Triple Bottom Line Abstrak: Transformasi menuju ekonomi berkelanjutan menjadi kebutuhan strategis di tengah tekanan krisis iklim, degradasi lingkungan, dan ketimpangan sosial. Inovasi teknologi dipandang sebagai motor utama untuk menyeimbangkan pertumbuhan ekonomi dengan pelestarian lingkungan dan inklusivitas sosial. Artikel ini bertujuan memetakan teknologi kunci yang mendukung ekonomi berkelanjutan, menganalisis strategi implementasinya pada sektor utama di Indonesia, serta mengevaluasi dampaknya pada dimensi ekonomi–lingkungan–sosial (triple bottom line). Penelitian menggunakan pendekatan kualitatif-deskriptif melalui kajian literatur dan analisis kasus pada sektor energi, pertanian, manufaktur, dan UMKM. Hasil menunjukkan bahwa AI, IoT, big data, blockchain, energi terbarukan, dan fintech hijau berkontribusi signifikan dalam meningkatkan efisiensi sumber daya, menurunkan emisi, memperkuat transparansi rantai pasok, serta memperluas akses pembiayaan usaha hijau. Tantangan utama meliputi kesiapan infrastruktur, biaya awal tinggi, literasi digital, regulasi yang belum adaptif, dan ketimpangan akses teknologi. Artikel ini merekomendasikan penguatan kebijakan insentif, pembangunan ekosistem inovasi lintas aktor, serta peningkatan kapasitas SDM digital-hijau untuk mempercepat pertumbuhan ekonomi hijau di Indonesia. Kata Kunci: Ekonomi Berkelanjutan, Inovasi Teknologi, Green Economy, Circular Economy, Indonesia, Triple Bottom Line